2002
DOI: 10.1203/00006450-200201000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Improved Neuroprotection with Hypothermia Delayed by 6 Hours Following Cerebral Hypoxia-Ischemia in the 14-Day-Old Rat

Abstract: Since hypothermia may be a potential treatment for perinatal cerebral hypoxic-ischemic injury, we used an established neonatal model of hypoxia-ischemia to determine the time after injury at which cooling had the best protective effect. Fourteen-day-old Wistar rats were subjected to right carotid artery ligation and hypoxia (8% O 2 for 90 min). Immediately at the end of hypoxia (defined as 0h), animals were either maintained at normal body temperature until sacrifice (normothermia) or subjected to hypothermia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 37 publications
1
42
0
1
Order By: Relevance
“…Hypothermia improves survival and neurologic outcomes in neonatal animal models of severe HI injury (4 -7), and in recently completed clinical trials of HI neonates when instituted within 6 h of birth (8 -11). Animal data shows that initiation of hypothermia between 6 and 12 h after HI reduces cerebral injury (12,13), perhaps moderating secondary injury cascades during a time when cellular recovery is still possible. However, some inflammatory mediators are merely delayed by hypothermia treatment (14), indicating that hypothermia may be most helpful in extending the therapeutic window after HI injury.…”
Section: H Ypoxic Ischemic (Hi) Injury In Neonates Occurs In Termmentioning
confidence: 99%
“…Hypothermia improves survival and neurologic outcomes in neonatal animal models of severe HI injury (4 -7), and in recently completed clinical trials of HI neonates when instituted within 6 h of birth (8 -11). Animal data shows that initiation of hypothermia between 6 and 12 h after HI reduces cerebral injury (12,13), perhaps moderating secondary injury cascades during a time when cellular recovery is still possible. However, some inflammatory mediators are merely delayed by hypothermia treatment (14), indicating that hypothermia may be most helpful in extending the therapeutic window after HI injury.…”
Section: H Ypoxic Ischemic (Hi) Injury In Neonates Occurs In Termmentioning
confidence: 99%
“…Experiments in animals have shown that a large number of treatments would reduce brain injury if given soon after the insult (1). Recently, moderate hypothermia to protect against brain injury has undergone vigorous investigation by many researchers around the world (2,4,6,7,31). Cooling the brain to approximately 32°C is one of several interventions that can be applied after HI to modify the process of brain cell death and so reduce brain damage.…”
Section: Time Course Of Brainstem Pathophysiology After Asphyxiamentioning
confidence: 99%
“…The 7-d-old rat with unilateral carotid artery ligation and subsequent exposure to 8% hypoxia is the most commonly used model to evaluate the efficacy of therapeutic interventions in the developing brain (12), and several studies have used this Rice-Vannucci model (RVM) to test the effects of HT (10,11,(13)(14)(15)(16)(17)(18)(19). However, an experimental design composed of a shorter duration of hypoxia, representing "mild" ischemic lesions, is not appropriate for evaluating the neuroprotective effect of HT against severe HIE.…”
Section: Introductionmentioning
confidence: 99%